Philonotis minuta (Bartramiaceae, Bryophyta) is Proposed as the Correct Name for P. brevifolia , and Recorded for the First Time in North America from California (U.S.A.) - Jimenez, Maria Soledad (2018)
The study of the type specimen of Bartramia minuta Taylor, a species described based on Ecuadorian samples that predates the recently resurrected Chilean Philonotis brevifolia Herzog shows that both names displayed the same set of diagnostic characters. In this contribution, P. minuta is proposed as the correct name of this taxon, a lectotype is selected, and its distribution is extended to North America, based on samples collected in California.